Cattle Diets Strongly Affect Nitrous Oxide in the Rumen - Katrin Gerlach (Sustainability, 2018)
This study aimed at assigning climate-relevant gaseous emissions from ruminants to animal- or feed-related origin. Three adult rumen-cannulated German Holstein steers and three forage types (corn silage (CS), alfalfa silage (AS) and grass hay (GH)) were used in a 3 × 3 Latin square design. Each period consisted of 12 days (d), during which animals received 10 kg dry matter/day of one forage as sole feed. Gaseous samples from forages and the steers´ rumen were taken and analyzed for CO2, CH4, and N2O using gas chromatography. There were large differences in the amounts of CO2 and N2O emitting from the forage types. Most N2O came from AS and only small amounts from GH and CS. Results indicate that fermented forages rich in nitrogen can release climate-relevant N2O. The highest CO2 amounts were measured in CS. Methane was not detected in any forage sample. Animals consuming CS showed slightly lower CH4 concentrations in the rumen gas sample than animals fed AS or GH. Big differences were found for ruminal N2O with the highest concentration after AS ingestion such that the N2O measured in the rumen seems to originate from the used feedstuff.